Effectivity and Safety Profile of Metformin as an Adjuvant Immunomodulator in Psoriasis: A Literature Review - Jessica Tjia; Eugenia Agnes Rombelayuk; Muh. Iqra Romadhan (Sumatera Medical Journal, 2025)
Background: Psoriasis is a chronic inflammatory skin disorder associated with an increased risk of comorbidities and reduced quality of life. Metformin, a first-line therapy for type 2 diabetes mellitus (T2DM), has been investigated for its potential as an adjuvant therapy for psoriasis. Objective: This literature review aims to explore the molecular mechanisms by which metformin exerts immunomodulatory effects and assess clinical studies that evaluate its efficacy and safety profile. Methods: A literature search was conducted in PubMed, MDPI, Epistemonikos, ScienceDirect, and Wiley Online Library, with the keywords: metformin AND psoriasis AND immunomodulator AND safety. Results: Qualitative synthesis revealed that metformin exhibits anti-inflammatory, anti-proliferative, and pro-apoptotic effects through induction of G0/G1 cycle arrest and  inhibition of mechanistic target of rapamycin (mTOR), nuclear factor-kappa B (NF-κB), and Raf/MEK/extracellular signal-regulated kinase (Raf/MEK/ERK) pathways. These mechanisms correlate with improvements in psoriasis severity indices, including Psoriasis Area Severity Index (PASI), Erythema, Scaling, and Induration (ESI), and Physician Global Assessment (PGA) scores (p < 0.05. A rare case of drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome has been reported. Conclusion: Metformin demonstrates potential as an adjuvant immunomodulatory treatment for psoriasis. However, a rare adverse effect highlights the need for careful patient selection and evaluation.